Effect of Eurycoma longifolia and eccentric exercise on quadriceps strength in elite rugby players / Ahmad Zawawi Zakaria - Ahmad Zawawi, Zakaria (2021)
Optimizing performance by resistance training over a limited amount of time was imperative in a training year plan. Superior effect of eccentric training has been documented but less known its influence on elite athletes which incorporated submaximal and supramaximal intensity eccentric that was essential for muscle strength and hypertrophy. Correspondingly, Eurycoma longifolia Jack (ElJ) supplementation has been shown to stimulate the production of the non-prohibited androgenic hormones, which was important for athletic performance in terms of muscular strength and size. However, investigation was not sufficiently vigorous on such effect of a supplement in elite athletes. Therefore, the major aim of this thesis was to examine the effects of ElJ supplementation when employing eccentric training on the physiological, physical, and performance changes among highly trained male Rugby Sevens players. Study one examined the short-term effects of ElJ supplementation on muscle function, hormones, and muscle damage. Participants (n=16) were randomly and equally placed into two groups, ElJ supplementation and placebo who consumed four 100-mg capsule a day for each for seven days prior to performing a leg press eccentric exercise using a 323-kg load (5-s eccentric contraction with the load, and without the load for concentric contractions) to failure. The results showed that testosterone and cortisol levels, creatine kinase activity, and vertical jump performances were not affected (p > 0.05) by ElJ supplementation, suggesting that no significant effects of ElJ supplementation on hormones, muscle damage markers, and exercise performance. To examine the influence of ElJ supplementation during actual training (i.e. athlete’s strength training programme), study two and three incorporated a progressive 6-week submaximal (75 to 100% of 1 repetition maximum [RM]), and 3-week supramaximal (110 to 130% of 1RM) eccentric training sing leg press exercise, respectively to examine the effects of ElJ supplementation (i.e. four 100-mg capsules a day) on the physiological, physical, and performance changes following each training period that conducted in a randomised, double-blinded, parallel design experiment (n=16). The two-factor mixed-design ANOVA revealed that hormone levels, eccentric and concentric leg press 1RM strength, isokinetic and isometric strength, and muscle thickness of the quadriceps did not differ (p > 0.05) between ElJ and placebo groups after each training period. It is important to note that there seems a tendency of ElJ groups in all studies to respond better than the placebo groups, without achieving a significant difference. Based on these findings, it can be concluded that ElJ supplementation provide limited benefit to various measures of physiological, physical, and performance among elite athletes in the present study. Irrespective of mechanisms, future research is necessary to determine if the results in the present study can be replicated and reconfirmed in order to better understand the roles of ElJ supplementation in conjunction with eccentric training modalities for sports performance.